The Relationship Between the Intensity of Reading the Qur'an on Learning Achievement - Khairan M Arif; Badrah Uyuni; Marliza Oktapiani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze whether UIA students have the habit and level of regularly reading the Qur'an every day, what are the factors that strengthen these habits, and how they relate to learning achievement. This research uses quantitative methods. Based on the research procedures used in this study, the research instruments will be the results of the pre-test conducted at the first meeting of the lecture and the post-test at the last meeting of the class, as well as measurements of attendance levels during the lecture process. The population used was students of the Islamic Education Study Program, Faculty of Islamic Religion, UIA, who recorded the basic level of understanding of the Qur'an and Tajweed. The results were found on student scores before and after the test. The correlation value between the two variables, the result of 0.613 means that the relationship is quite strong and positive. From the calculation results of the value of thit ttabel (-19,6402,0369)   Pre-test has a significant effect on the Post Test. They are increasing the intensity of reading the Qur'an in UIA students with programs and stimulation that can measure direct creation and development of habits and love to read the Qur'an because of the willingness factor to improve the reading of the Qur'an and be consistent in attendance during lectures.